Analysis of the Influence of Capital Expenditure and Human Development Index on Per Capita Income: Evidence from City Regency Panel Data in Aceh, Indonesia - Fadhlurrahman, Al Haqqi; Amri, Khairul; Fitri, Cut Dian (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the effect of capital expenditure and the human development index (HDI) on per capita income in Aceh Province, using panel data from 23 districts/cities during the period 2011–2023. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach, which was selected based on the results of the Chow and Hausman test. The results show that capital expenditure has a positive and significant effect on per capita income, indicating that the effectiveness of the allocation of this expenditure is optimal in driving local economic growth. Likewise, the HDI has a positive and significant effect, indicating that improving the quality of education, health, and people's living standards contributes significantly to increasing per capita income. These findings emphasize the synergy between physical development through capital expenditure and human development through increasing the HDI to drive inclusive and sustainable economic growth in Aceh Province.